Biopharmacological studies of the aqueous extract of Lepidium sativum seeds in alloxan - induced diabetes in rats - Al-khazraji, Shahbaa M. (The Iraqi Journal of Veterinary Medicine, 2012)
Garden cress (Lepidium sativum) seeds are considered extensively in the folk medicine as anantidiabetic agent in many countries. The current investigations focuses attention on theglucose and lipid lowering effect of the aqueous extract of L. sativum seeds on experimentally induced diabetes in rats. The biochemical parameters studied were plasma glucose, insulin, totalcholesterol,triglycerides,phospholipids,hemoglobin, and glycosylated hemoglobin.In addition body weight and renal glucose reabsorption were notified. Aqueous extract of L. sativum were orally administered daily for 30 days in a dose of 20 mg / kg body weight to alloxan – diabetic rats , and a significant reduction in the parameters measured was investigated compared to diabetic rats. Meanwhile, Glibinclamide was used as standard reference drug. In cznclusion , L. sativum seeds possess a hypoglycaemic with concurrent hypolipidemic effect in diabetic states , and may further suggests thatL. Sativum may be useful in the therapy andmanagements of diabetic hyperlipidemia through reducing lipids levels .